Integrated transcriptomics and metabolomics provides insights into the Nicotiana tabacum response to heat stress - Chen, Hao; Qiu, Shaoxin; Chen, Yuanping; Li, Jiqin; Xu, Tingyu; Zhong, Pingzhan; Shao, Xiuhong; Xu, Shihuan; Ma, Zhuwen; Huang, Zhenrui; Pan, Xiaoying (Frontiers in Plant Science, 2024)
Heat stress is a prevalent factor that significantly damages crops, especially with the ongoing global warming and increasing frequency of extreme weather events.Tobacco is particularly sensitive to temperature fluctuations, experiencing reduced yield and quality under high temperatures. However, the underlying molecular mechanisms of heat resistance in tobacco remain poorly understood. This study comprehensively analyzed biochemical, transcriptomic, and metabolomic responses to heat stress on the root and shoot of the tobacco cultivar K326 compared to control conditions. Heat stress significantly increased the activities of antioxidant enzymes (CAT, POD, and SOD) and levels of osmotic mediators (soluble sugars, sucrose, and proline) in the shoot. Furthermore, transcriptome analysis identified 13,176 differentially expressed genes (DEGs) in the root (6,129 up-regulated and 7,047 downregulated) and 12,283 DEGs (6,621 up-regulated and 5,662 down-regulated) in the shoot. The root had 24 enriched KEGG pathways, including phenylpropanoid metabolism, while the shoot had 32 significant pathways, such as galactose metabolism and MAPK signaling. The metabolomic data identified 647 metabolites in the root and 932 in the shoot, with carbohydrates and amino acids being the main categories. The root had 116 differentially abundant metabolites (DAMs) (107 up-regulated and 9 down-regulated), and the shoot contained 256 DAMs (251 up-regulated and 5 downregulated). Joint transcriptome and metabolome analysis showed that galactose metabolism and starch and sucrose metabolism were co-enriched in both tissues. In contrast, amino sugar and nucleotide sugar metabolism was enriched in the root, and purine metabolism in the shoot. The purine metabolic pathway in the shoot can modulate the expression of MYB transcription factors by influencing ABA synthesis and signaling, thereby controlling the accumulation of HSPs, raffinose, sucrose, and trehalose to enhance heat tolerance. Furthermore, NtMYB78, an MYB transcription factor, enhances tolerance for heat stress in tobacco. This research offers a foundational framework for investigating and implementing heat-resistant genes and metabolic pathways in the root and shoot of tobacco seedlings.